Komunikaty: An Experimental Investigation of Or and Jr Resistance Curves and COA by Replication Technique - Xuewei, S.; Zhiyuan, Ch.; Bingye, X. (Engineering Transactions, 1984)
Silicone rubber replicas are used to investigate the crack growth problems in a stainless steel under various loading conditions. These replicas are analyzed by means of the optical and electron microscopy. Certain parameters describing the elastic-plastic fracture of a material are examined in greater detail.